Effects of vegetation height and relative submergence for rigid submerged vegetation on flow structure in open channel - Wang, Zhongyu; Zhang, Huayong; He, Xing; Jiang, Qi; Xu, Weigang; Tian, Wang (Earth Sciences Research Journal, 2022)
<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: 宋体; mso-fareast-theme-font: minor-fareast; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">In this research, the vegetation height and a concept of relative submergence are adapted to experimentally investigate the effects of rigid submerged vegetation on flow structure. The results reveal that the relative submergence presents decreasing trend along the submerged vegetation section and the average relative submergence follows a power functional decreasing relationship regarding to the increase of vegetation height. After the exit of vegetation block, the water depths for the vegetated cases resume to the level and trend of the case without vegetation. The differences between the maximum and minimum water depths for the submerged cases follow a linear relationship with vegetation height and a negative power functional relationship with the average relative submergence, with which, the raised water depths due to rigid submerged vegetation can be predicted under similar hydraulic and vegetation conditions to the present research. Due to the retardance of vegetation block, the differences between the maximum and minimum flow velocities increase with the vegetation height as the maximum values change slightly and the minimum values decrease continuously. The findings of the research may improve the comprehensive understandings of open channel hydraulic behaviors affected by rigid submerged vegetation and give some guidance to the river ecological restorations.